Corruptio Legis in Indonesian Legal Politics: A Legisprudential Analytical Approach - Muhamad Pelengkahu (Faculty of Law, Universitas Lampung, 2025)
This study conceptualises Corruptio Legis as a form of structural corruption operating within Indonesia’s legislative process, where formally valid procedures conceal substantive distortions of law, justice, and constitutional democracy. Using Wintgens’ legisprudence, Ekins’ theory of legislative intention, and Tuori’s ratio–voluntas framework, the analysis identifies key patterns of distortion, including legislative subordination to party elites, transactional lawmaking, and the marginalisation of public deliberation. Case studies of the stalled Asset Confiscation Bill and the Job Creation Law illustrate how oligarchic political interests displace public reason in lawmaking. The study proposes a four-step Corruptio Legisprudential Diagnosis Formula and advocates a Legislative Impact Assessment grounded in this framework to ensure that legislation is guided by rational deliberation rather than power-based interests.